2020
DOI: 10.1111/all.14133
|View full text |Cite
|
Sign up to set email alerts
|

Allergen‐specific immunotherapy boosts allergen‐specific IgD production in house dust mite‐sensitized asthmatic patients

Abstract: Whereas the biology of IgG, IgA, and IgE has been extensively studied in allergic diseases, the regulation and function of IgD remain poorly investigated. IgG4 is a blocking antibody, which prevents the cross-linking of receptor-bound IgE. IgD is unable to recruit complement protein which is similar to mucosal IgA. 1 IgD was shown to increase Th2 cell polarization in germinal centers, boosting Th2 cytokine production. 2 IgD-activated basophils also enhance IgG1 and IgE production by allergen-specific B cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 10 publications
1
14
0
1
Order By: Relevance
“…The longitudinal change in Der p 2‐specific IgE/IgD ratio was similar to that in Der p 2‐specific IgE/IgG4 ratio. Asthma symptoms were improving during the AIT process, which also correlated with allergen‐specific B‐cell responses 178 …”
Section: Novel Treatments Driven By Asthma Endotypesmentioning
confidence: 87%
See 1 more Smart Citation
“…The longitudinal change in Der p 2‐specific IgE/IgD ratio was similar to that in Der p 2‐specific IgE/IgG4 ratio. Asthma symptoms were improving during the AIT process, which also correlated with allergen‐specific B‐cell responses 178 …”
Section: Novel Treatments Driven By Asthma Endotypesmentioning
confidence: 87%
“…The longitudinal change in Der p 2-specific IgE/IgD ratio was similar to that in Der p 2-specific IgE/IgG4 ratio. Asthma symptoms were improving during the AIT process, which also correlated with allergen-specific B-cell responses 178. Many retrospective AIT studies investigated the risk of new-onset asthma, the relative risk of medication dispensing for asthma and its potential progression among multimorbid allergic subjects.It was found that use of sublingual allergen immunotherapy tablets for pollen allergy for the treatment of AR could reduce the prevalence of asthma, decrease asthma medication usage, and also slow down progression of asthma in comparison with a group receiving only symptomatic AR medication [179][180][181].…”
mentioning
confidence: 99%
“…Interestingly, serum IgD antibodies against milk‐derived allergens alpha s1‐casein, beta‐lactoglobulin were increased in cow's milk allergic children after oral immunotherapy 73 . Similarly, in a cohort of HDM AIT‐treated patients, allergen‐specific IgD was significantly increased after 2 years of treatment 76 . Although the exact contribution of allergen‐specific IgD antibodies in the context of IgE‐mediated allergic inflammation remains incompletely understood, the currently available data suggest that IgD contributes to allergic sensitization through enhancing IgE production.…”
Section: Protective Antibody Responses In Food Allergymentioning
confidence: 95%
“…73 Similarly, in a cohort of HDM AIT-treated patients, allergen-specific IgD was significantly increased after 2 years of treatment. 76 Although the exact contribution of allergen-specific IgD antibodies in the context of IgE-mediated allergic inflammation remains incompletely understood, the currently available data suggest that IgD contributes to allergic sensitization through enhancing IgE production. On the other hand, IgD may also play a role in the induction of allergen tolerance by suppressing IgE-mediated basophil (and potentially also mast cell) degranulation.…”
Section: Protec Tive Antibody Re S P On S E S In Food Allergymentioning
confidence: 99%
“…Asthma symptoms were improving during the AIT process, which also correlated with allergen-specific B cell responses. 177 Many retrospective AIT studies investigated the risk of new-onset asthma, the relative risk of medication dispensing for asthma and its potential progression among multimorbid allergic subjects. It was found that use of sublingual allergen immunotherapy tablets for pollen allergy for the treatment of allergic rhinitis could reduce the prevalence of asthma, decrease asthma medication usage and also slow progression of asthma in comparison to a group receiving only symptomatic allergic rhinitis medication.…”
Section: Novel Treatments Driven By Asthma Endotypesmentioning
confidence: 99%